Contra trading in Bursa Malaysia Securities Berhad: a Sharīʿah and legal appraisal - Noor Suhaida Kasri; Burhanuddin Lukman (ISRA International Journal of Islamic Finance, 2017)
Purpose: The purpose of this paper is to analyze the practice of contra trading in Bursa Malaysia Securities Berhad. Through a critical examination of the practice, it aims to discuss the issues from the angles of Sharīʿah and Malaysian common law. Design/methodology/approach The paper uses a qualitative research methodology. The information on the practice of contra trading is obtained through the Bursa Malaysia Securities Berhad's website and literature as well as series of meetings and discussions held with Bursa Malaysia Securities Berhad. In comprehending and dissecting the Sharīʿah and legal issues, classical along with contemporary Sharīʿah literature including local and international Sharīʿah advisory bodies' resolutions and standards have been referred to. The Sharīʿah analysis of these issues is further supported by reference to the statute and by-laws of Bursa Malaysia Securities Berhad as well as other related legal literature. Findings This paper finds that contra trading involves a real sale and purchase of shares; the shares are not taken into the possession of the contra trader, neither physically nor constructively; the liability of shares is not transferred to the contra trader; though the practice of profiting in contra trading may contradict the prohibition on profiting without bearing liability, the permissibility of contra trading could still be argued from the contextual approach of public interest (maṣlaḥah) and needs (hājah); and contra trading is not gambling. Research limitations/implications This paper is limited in its analysis to only Sharīʿah and legal perspectives. It does not cover a thorough empirical and quantitative investigation that would measure the extent of the public needs for contra trading and the real benefits that contra trading brings about to the society in the long run. Such studies will further demonstrate whether contra trading deserves a relaxation from the strict Sharīʿah ruling thus affirming the issue of permissibility of contra trading. Moving forward, this paper recommends ways to address the predicaments faced in the contra trading practices as well important research areas that could be taken up in future. Originality/value This paper provides an in-depth investigation of the practice of contra trading at the Bursa Malaysia Securities Berhad from the angles of Sharīʿah and common law.
Keywords: 330; broker; contra trading; exchange; Legal; shares